Legal Protection of Consumer Personal Data in Business in the Digital Era - Dian Arifin; Wiwik Sri Widiarty; Richard Marolop Nainggolan (International Journal Labs, 2025)
The misuse of personal data by certain individuals, including individuals within business entities, has become a form of loss for many people, growing alongside advances in digital technology, where various activities can now be conducted digitally. Since 2021, numerous cases of consumer data breaches have occurred. Although the Personal Data Protection Law (PDP) has been enacted, its implementation still faces various obstacles, such as a lack of effective oversight, the absence of an independent authority fully responsible for personal data protection, and a lack of awareness among digital businesses regarding compliance with the new regulations. The type of study undertaken is a normative legal study (library legal research), as indicated by the title of this thesis. The data sources for this research are secondary data. Legal concepts, legal ideas, legal doctrines, and relevant regulations can be cited, copied, and analyzed to obtain secondary data from library research. The approach used in this thesis is the normative legal approach. The problem in this thesis discusses the Legal Certainty for Consumers Who Experience Personal Data Violations in Digital Business Transactions Based on Law Number 27 of 2022 concerning Personal Data Protection and Legal Protection Efforts for Personal Data Consumers Harmed by Digital Business Transactions. The analysis and discussion found that Legal Certainty for Consumers who experience Personal Data Violations in Digital Business Transactions based on Law Number 27 of 2022 concerning Personal Data Protection can be seen in the provisions of Articles 7 to 14 of the PDP Law. Specifically, the legal certainty of consumer protection for their personal data can be seen in the provisions of Article 12 Paragraph (1) of the PDP Law, which essentially states that personal data subjects have the right to sue and receive compensation for violations of the processing of Personal Data about them. In addition, everyone has the right to view, change, delete, and limit the processing method of personal data, in accordance with the provisions of Articles 15 to 20 of the PDP Law. The Consumer Protection Law does not include a single article regulating the legal certainty of consumer personal data protection. The provisions of Article 45 of the Consumer Protection Law only state that Consumers can file a lawsuit based on Article 45 of the Consumer Protection Law if they feel they have been harmed by Business Actors.